The Effectiveness of Mediation in the Syar'iyah Court of Idi in Divorce Cases - Zulfikar, Zulfikar; Aminah, Aminah; Azharuddin, Azharuddin (Ahlika: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This study discusses the Effectiveness of Mediation Implementation at the Idi Sharia Court in Divorce Cases. Mediation in divorce cases at the Idi Sharia Court ends peacefully very little, so the success rate of mediation is very low. The problem in this study is how effective is the implementation of mediation in divorce cases and what factors support and inhibit the success of mediation in divorce cases at the Idi Sharia Court, the purpose of this study is to analyze the effectiveness of the implementation of mediation in divorce cases and what factors support and inhibit the success of mediation in divorce cases at the Idi Sharia Court. The research method used in this study is empirical juridical with a legal sociology approach. Data collection techniques through observation, interviews, and documentation. The informants in this study were Judge Mediators at the Idi Sharia Court. The results of the study: 1) The implementation of mediation at the Idi Sharia Court has not been effective but the procedure is in accordance with PERMA No. 1 In 2016, Mediation that was successfully reconciled in 2020-2023 from 498 divorce cases, only 2 cases were successfully reconciled in their entirety. 2) Obstacles and Challenges faced by the judge mediator are that there are no Non-Judge Mediator personnel, then the main problem of the case has been left for too long so that it is difficult to reconcile, and there is a lack of public awareness of mediation, both the function and role of the mediator. The conclusion is that mediation at the Idi Sharia Court can be said to be ineffective because the results of Mediation very rarely end in peace, the obstacles and challenges faced by the judge mediator at the Idi Sharia Court One of them is that there are no Non-Judge Mediator personnel and a lack of public awareness of the benefits of mediation. Abstract: Penelitian ini membahas Efektivitas Pelaksanaan Mediasi Pada Mahkamah Syar’iyah Idi Dalam Perkara Perceraian.  Mediasi dalam kasus perceraian pada Mahkamah Syar’iyah Idi berakhir damai sangat sedikit, sehingga tingkat keberhasilan mediasi sangat rendah. Permasalahan dalam Penelitian ini yaitu bagaimana efektivitas pelaksanaan mediasi dalam perkara perceraian dan faktor-faktor apa saja yang menjadi pendukung dan penghambat keberhasilan mediasi pada perkara perceraian di Mahkamah Syar’iyah Idi, tujuan penelitian ini untuk menganalisis efektivitas pelaksanaan mediasi dalam perkara perceraian dan faktor-faktor apa saja yang menjadi pendukung dan penghambat keberhasilan mediasi pada perkara perceraian di Mahkamah Syar’iyah Idi. Metode penelitian yang digunakan dalam penelitian ini adalah yuridis empiris dengan pendekatan kulitatif. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Informan dalam penelitian ini adalah Mediator Hakim di Mahkamah Syar’iyah Idi. Hasil dari penelitian: 1) Pelaksanaan mediasi di Mahkamah Syar’iyah Idi belum berjalan efektif namun prosedurnya sudah sesuai dengan PERMA No. 1 Tahun 2016, Mediasi yang berhasil didamaikan pada Tahun 2020-2023 dari 498 kasus perceraian hanya 2 kasus yang berhasil didamaikan selurunya. 2) Hambatan dan Tantangan yang dihadapi oleh mediator hakim ialah belum terdapat personil Mediator Non Hakim, kemudian permasalahan pokok perkara sudah terlalu lama dibiarkan sehingga susah untuk didamaikan, serta kurangnya kesadaran masyarakat tentang mediasi baik  fungsi dan peran mediator. Kesimpulannya ialah mediasi di Mahkamah Syar’iyah Idi dapat dikatakan belum efektif karena hasil Mediasi sangat sedikit berakhir damai, hambatan dan tantangan yang dihadapi oleh mediator hakim di Mahkamah Syar’yah Idi Salah Satunya ialah belum terdapat personil Mediator Non Hakim dan kurangnya kesadaran masyarakat akan manfaat mediasi.